Peran Pustakawan Dalam Memotivasi Siswa Memanfaatkan Perpustakaan SMK Tamansiswa Padang - Elferida, Kristi; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper focuses on the role of librarians in motivating students to use the library of Tamansiswa SMK Padang. This study aims to: (1) find out what is being done and by school side also the of librarian Tamansiswa SMK Padang motivate the students to use the library and, (2) to determine what obstacles faced in motivating students use the library. The analyzing of data has been done by descriptive way. Based on the analyzing of data, it was concluded as follows. First, the efforts were made by ​​librarians in motivating students use the library are: (1) librarians conduct library-related activities such as holding a short story writing competition for students, (2) the librarian launce the guidance on the function of the library for the student, (3) librarians provide prizes to students who often use the library, which adds to the period of borrowing books for students. Second, the constraints faced by librarians in motivating students use the library are: (1) the lack of means of promotion in the library of Tamansiswa SMK Padang, (2) donations, (3) lack of cooperation between the school and the foundation, (4) lack of librarians skill; (5) the students interest in reading are weak. Keywords: librarian; motivate students to use library